2015
DOI: 10.1681/asn.2015030279
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CKD on Colonic Microbial Metabolism

Abstract: There is increasing interest in the colonic microbiota as a relevant source of uremic retention solutes accumulating in CKD. Renal disease can also profoundly affect the colonic microenvironment and has been associated with a distinct colonic microbial composition. However, the influence of CKD on the colonic microbial metabolism is largely unknown. Therefore, we studied fecal metabolite profiles of hemodialysis patients and healthy controls using a gas chromatography-mass spectrometry method. We observed a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 37 publications
6
84
0
Order By: Relevance
“…As far as we know, there is only one study in humans on microbial metabolism in individuals with CKD. Poesen et al [94] investigated fecal metabolite profiles of hemodialysis patients and healthy individuals and observed distinct colonic microbial metabolism between these two groups. They found upregulated generation of p-cresol, indoles, aldehydes, benzenes, furans, and branched-chain, mediumchain, and short-chain fatty acids and a reduced generation of ketones in patients on hemodialysis.…”
Section: Gut Microbiota In Ckdmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we know, there is only one study in humans on microbial metabolism in individuals with CKD. Poesen et al [94] investigated fecal metabolite profiles of hemodialysis patients and healthy individuals and observed distinct colonic microbial metabolism between these two groups. They found upregulated generation of p-cresol, indoles, aldehydes, benzenes, furans, and branched-chain, mediumchain, and short-chain fatty acids and a reduced generation of ketones in patients on hemodialysis.…”
Section: Gut Microbiota In Ckdmentioning
confidence: 99%
“…The clinical impact of these alterations is unknown for the majority of these fecal metabolites. Studies with uremic rats also demonstrated significant differences in fecal metabolite profiles, indicating an important influence of loss of renal function [94,95]. However, in humans, in contrast to rats, when the researchers compared the patients on hemodialysis with household contacts on the same diet, the influence of decreased renal function was inferior to the external factors, such as the diet [94].…”
Section: Gut Microbiota In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NMR is able to measure approximately 8% and gas chromatography MS is able to measure approximately 7% of the human urine metabolomes [4] . For the urinary metabolomics, effects of the kidney function as well as the metabolic function of the body which may affect secretion and reabsorption of the circulating metabolites may confound the final results [42] .…”
Section: Limitations Of Urinary Metabolomics In Gi Disordersmentioning
confidence: 99%
“…Metabolomics of volatile vs non-volatile compounds is also an important area which should be considered. In addition, the effects of urinary diseases on GI system and microbiota as what has been recently observed in patients with chronic kidney diseases [42] should be taken into account when interpreting urinary metabolomics studies.…”
Section: Future Directionmentioning
confidence: 99%